Pengaruh Pendapatan Domestik Bruto, Suku Bunga Dan Indeks Harga Konsumen Terhadap Permintaan Uang Di Indonesia - Fadhil Dwi Ivanof; Menik Kurnia Siwi (Universitas Negeri Padang, 2022)
This study aims to analyze the effect of gross domestic income, interest rates, and the consumer price index on the demand for money in Indonesia from 2011 to 2020. This study uses time series data with an Ordinary Least Square (OLS) approach. The model estimation results show that the variables of gross domestic income, interest rates, and the consumer price index simultaneously or jointly affect the demand for money in Indonesia. Meanwhile, partially the gross domestic income variable has a positive and significant effect on the demand for money in Indonesia. The interest rate variable partially has a negative and significant effect on the demand for money in Indonesia. The consumer price index variable partially has a negative and significant effect on the demand for money in Indonesia.